When Satisfaction Is Not Enough: The Mediating Role of Trust in Customer Loyalty within B2B Logistics Services - Robby Surakhman; Ronald Suryaputra; Widi Dewi Ruspitasari (Al-Qalam Institue, 2026)
This study aims to examine the limitations of satisfaction-based loyalty models by investigating the fundamental role of trust in shaping customer loyalty within B2B service markets. Specifically, it assesses whether service quality and price perception remain effective drivers of customer loyalty in long-term, high-value business relationships. A quantitative research design was employed, with data collected from 66 strategic B2B customers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that trust is the only variable with a direct and significant effect on customer loyalty, while service quality and price perception do not exhibit significant direct influences. Although price perception significantly affects customer satisfaction, satisfaction does not mediate the relationships between service quality, price perception, trust, and customer loyalty. These findings indicate that customer satisfaction functions primarily as an evaluative outcome rather than a mechanism that converts service performance into sustained loyalty. This study contributes theoretically by repositioning trust as the central relational governance mechanism underlying B2B customer loyalty and reconceptualizing satisfaction as a non-mediating construct. Managerially, the findings suggest that firms serving strategic B2B customers should prioritize trust-building, relational governance, and long-term relationship stability over short-term service or pricing optimization.